Calculating the utility of attacks against ballistic missile transporter-erector-launchers - Shaver, R. D. (Russell D.); Mesic, Richard, 1943-; Project Air Force (U.S.). Force Modernization and Employment Program; Rand Corporation; United States. Air Force (Santa Monica, CA : RAND, 1995)
Calculating the utility of attacks against ballistic missile transporter-erector-launchers (TELs) associated with the proliferation of theater ballistic missiles (TBMs) can play a role in sharply reducing the prospective threat size. For initial inventories of, say, 10 TBMs per TEL, reductions of some 80 percent in missiles launched are possible with probabilities of successful postlaunch TEL kill of about 0.5. Combined prelaunch and postlaunch attacks against TELs act synergistically, enhancing the overall effectiveness. A set of equations (and their derivations) is provided to allow the reader to calculate additional outcomes.
"Project Air Force."
Includes bibliographical references.
Also available on the internet via WWW in PDF format.
Description based on print version record.
Keywords: Ballistic missile defenses -- Combat survivability -- Statistical methods